Flood Modeling Assessment: A Case of Bishnumati River - Dangol, Noor (Journal on Geoinformatics, Nepal, 2020)
Flood, a common water induced disaster of a monsoon season, is the recurring phenomenon in Nepal. To study this disaster, different flood modelling had been conducted for different river basins following different modelling tools. This study describes the technical approach of probable flood vulnerability and hazard analysis of Bishnumati river catchment and analyze the result with previous study done for the same study area. The method adopted for previous study in 2009 was adopted in this study as well in order to compare the results. One dimensional hydraulic model HEC-RAS with HEC GeoRAS interface in co-ordination with Arc GIS was applied for the analysis.. Hazard maps, landuse vulnerability maps of various return periods (10 Yrs, 20Yrs, 50Yrs and 100Yrs), were prepared in ArcGIS. The results of flood frequency analyzed by WECS/ DHM method showed discharges of 445 m³/s, 541m³/s, 648m/s, 725 m³/s for 10, 20, 50 and 100 years return period floods. The primary data of the study showed most of the flooding area had water depth greater than 3m. The assessment of the flood inundated area showed that large percentage of vulnerable area lied in built up areas followed by barren land.